Estimation of Lipid Profile among Hypothyroidism Patients Attending OPD in a Tertiary Care Centre at Puducherry - Bharath Kumar Nanyampalli; S. Kasipandian; Bhanu Priya; Naveen Naik (The Bioscan, 2025)
Background: In the general population, hypothyroidism both overt and subclinical is a common endocrine condition. Elevated total cholesterol, triglycerides, or low HDL levels are signs of dyslipidemia, which is a significant risk factor for cardiovascular diseases (CVD), especially coronary heart disease (CHD). Higher TC and TC/HDL ratios are associated with increased risk. The morbidity and mortality associated with CVD can be decreased by early dyslipidemia identification and treatment. In 1930, it was discovered that thyroid dysfunction and lipid abnormalities were related; hypothyroidism frequently resulted in high levels of TC and LDL-C. This study was carried out to quantify the frequency of hypothyroidism and evaluate the severity of related dyslipidemia among OPD patients, given the high prevalence of the condition in India. Materials and Methods: In a Puducherry Tertiary Care Centre, 71 hypothyroid patients who were at least 18 years old participated in a planned cross-sectional study. The purpose of the study was to evaluate the lipid profiles of patients who visited the General Medicine Outpatient Department. Convenient sampling was used to choose participants, and a standardized questionnaire was used for interviews to gather clinical and sociodemographic information. Epi-info software version 7.2.2.6 was used for data analysis and blood investigations. Results: In this study group, 19.7% had subclinical hypothyroidism and 80.3% had overt hypothyroidism, with hypercholesterolemia (16.9%), hypertriglyceridemia (23.9%), low HDL (100%), high LDL (38%), and high VLDL (70.4%) with HDL and VLDL abnormalities being most significant. A strong association between hypothyroidism and dyslipidemia was observed, highlighting increased risk. Diabetes and hypertension were the most common comorbidities, while CKD patients showed elevated lipid and thyroid parameters. Overweight and obese individuals had higher lipid (except TC) and thyroid (except FT3) levels. The study underscores the need for routine dyslipidemia screening in thyroid patients for effective integrated management. KEYWORDS Lipid profile, hypothyroidism, dyslipidemia